Kontrola finansowa i audyt wewnętrzny w samorządzie terytorialnym - Sołtyk, Piotr (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: For several years in Polish public administration, the new notion of internal audit has existed. He is the result of adaptation of to undertaken in the face of European Union obligations in the Polish side. The internal Audit of territorial council is the element of protection of social business in range of the dysponowaia the public centres. The activity of audit differs from traditional financial control with schedule of workings, the system approach in received to investigation area as well as the advisory testified in the face management of individual actions.